How Departments of Economics Evaluate Teaching - Becker, William E; Watts, Michael (American Economic Review, 1999)
Based on results from a 1999 national survey, William Becker and Michael Watts found that student evaluations of teaching were by far the most widely used, and often the only method used by economics departments, to evaluate teaching in undergraduate economics courses. To investigate whether departments of economics have moved beyond the use of student evaluations of teaching, in 2011 the current authors conducted a national survey of departments based largely on questions used in the 1999 survey. The surveys included items on how courses and teaching are evaluated, and on how that information is used in departmental promotion and salary decisions.